Analfabetismo funcional, alfabetização e letramento: ações da escola na produção de pesquisas entre 2011 e 2016 - Araújo, Luciane de Sousa Lopes (2018)
This paper deals with the relation between school actions and functional illiteracy. The interest in the subject took place when observing that a significant portion of students of Brazil’s public schools are in a situation of school failure. This fact is reflected in publications such as those published by INAF (National Indicator of Functional Literacy), which show that a large part of Brazil’s population is in the condition of functional illiterates. The purpose of this dissertation was to investigate what academic production - dissertations and theses - has obtained on functional illiteracy and on literacy, and how these productions evaluate the effectiveness of the methods. For that, a survey of investigations on functional illiteracy, teaching methods and literacy and alphabetization, expressed in dissertations and theses defended in postgraduate programs in Brazil, was carried out. We also looked for research carried out in Brazilian universities that discussed the student's relationship with knowledge, teacher training and public policies related to literacy and alphabetization. This research has as background the theoretical discussion between Capovilla and Seabra and Emília Ferreiro regarding the methods of literacy, which becomes a fundamental discussion for teacher training courses, as well as for alfabetization and literacy, according to Magda Soares and Roxane Rojo. The survey pointed out the importance of experiences with situations of literacy in their daily lives for all within the school, especially for those who had little access to literate culture. The initial hypothesis that there is no interest in studying in schools, actions aimed at combating functional illiteracy was confirmed and it was not possible to identify in the analyzed studies - dissertations and theses - actions and discussions, concerning both the high rates of illiteracy and functional illiteracy within the school, as to the ways of reducing or eliminating such difficulty of the Brazilian children and young people in the space of the institution